2015
DOI: 10.1002/ajpa.22798
|View full text |Cite
|
Sign up to set email alerts
|

Association of protein intakes and variation of diet‐scalp hair nitrogen isotopic discrimination factor in Papua New Guinea highlanders

Abstract: We hypothesize that a combination of several factors, which presumably included urea recycling and amino acid and protein recycling and/or de novo synthesis during metabolic processes, altered the Δ(15) N values of the participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Another advantage pertains the technical and ethical easiness of hair collection from the book, which is not usually be regarded as destruction of cultural properties in contrast to the case of archaeological skeletons. Moreover, isotopic studies of contemporary people are usually done with hair samples because of the technical and ethical easiness of hair collection 21 25 ; thus, direct comparison of the isotope ratios with the same tissue-specific TDF is possible when the hairs are used for the study of past people. This is important given that inter-tissue and inter-species variations in TDF were recently shown as more considerable than previously believed based on earlier studies 24 , 25 , 45 47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another advantage pertains the technical and ethical easiness of hair collection from the book, which is not usually be regarded as destruction of cultural properties in contrast to the case of archaeological skeletons. Moreover, isotopic studies of contemporary people are usually done with hair samples because of the technical and ethical easiness of hair collection 21 25 ; thus, direct comparison of the isotope ratios with the same tissue-specific TDF is possible when the hairs are used for the study of past people. This is important given that inter-tissue and inter-species variations in TDF were recently shown as more considerable than previously believed based on earlier studies 24 , 25 , 45 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, isotopic studies of contemporary people are usually done with hair samples because of the technical and ethical easiness of hair collection 21 25 ; thus, direct comparison of the isotope ratios with the same tissue-specific TDF is possible when the hairs are used for the study of past people. This is important given that inter-tissue and inter-species variations in TDF were recently shown as more considerable than previously believed based on earlier studies 24 , 25 , 45 47 . Books published in the early modern Japan remain massively available 28 , 29 , which has the potential to be used as ideal samples for large data analyses to test numerous hypotheses on regional variations and temporal changes of the eating habits and cuisines in the early modern Japan 3 – 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As d 15 N values of individual amino acids may reflect aspects other than diet, such as physiology or possibly illness (Styring et al, 2010;Reitsema, 2013;Naito et al, 2015), the observed partitioning in PCA may represent some difference in physiological traits among the fossil bears ( Fig. 6 and S2).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the degree of isotopic offsets in chimpanzees is essential in order to compare the isotopic ratios of a chimpanzee's tissues and food sources. The carbon and nitrogen offset values have been particularly well studied in humans; however, only a few studies have been reported for nonhuman primates (Table ) …”
Section: Carbon and Nitrogen Isotopic Offset Values (As ‰) Between DImentioning
confidence: 99%